Impaired Attention in Children with Obstructive Sleep Apnea: A Preliminary Study of Behavior Combined with Neuroelectrophysiology - Wu Y; Wang C; Jiang Y; Zhang Y; Zheng L; Ning XL; Xu Z (Nature and Science of Sleep)
Yunxiao Wu,1,2 Changming Wang,3 Yingchao Jiang,4 Ya Zhang,5 Li Zheng,2 Xiao-lin Ning,1,6– 8 Zhifei Xu5 1School of Instrumentation Science and Optoelectronic Engineering, Beihang University, Beijing, 100191, People’s Republic of China; 2Department of Otolaryngology, Head and Neck Surgery, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, 100045, People’s Republic of China; 3Department of Neurosurgery, Xuanwu Hospital, Capital Medical University, Beijing, 100053, People’s Republic of China; 4College of Psychology and Mental Health, North China University of Science and Technology, Tangshan, 063210, People’s Republic of China; 5Clinical Department of National Clinical Research Center for Respiratory Diseases, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, Beijing, 100045, People’s Republic of China; 6Key Laboratory of Ultra-Weak Magnetic Field Measurement Technology, Ministry of Education, School of Instrumentation and Optoelectronic Engineering, Beihang University, Beijing, 100191, People’s Republic of China; 7Institute of Large-Scale Scientific Facility and Centre for Zero Magnetic Field Science, Beihang University, Hangzhou, 310051, People’s Republic of China; 8National Institute of Extremely-Weak Magnetic Field Infrastructure, Hangzhou, 3100051, People’s Republic of ChinaCorrespondence: Xiao-lin Ning, Beihang University, 37 Xueyuan Road, Haidian District, Beijing, 100191, People’s Republic of China, Tel +8613691352196, Email ningxiaolin@buaa.edu.cn Zhifei Xu, Beijing Children’s Hospital, Capital Medical University, National Center for Children’s Health, 56 Nanlishi Road, Xicheng, Beijing, 100045, People’s Republic of China, Tel +8613521660077, Email zhifeixu@aliyun.comObjective: To investigate how attention is affected in children with obstructive sleep apnea (OSA) using the attention network test (ANT) combined with event-related potential (ERP) and time-frequency analysis.Methods: Eighty-seven children aged 6– 11 years with symptoms of snoring or mouth breathing during sleep were recruited from the Sleep Center of Beijing Children’s Hospital from May to July, 2023. All participants completed the Mini-mental State Examination and Attention Deficit Hyperactivity Disorder rating scale. We acquired 32-lead electroencephalography (EEG) data while participants performed the ANT, followed by Polysomnography.Results: Of the 87 children, 21 had no OSA, 49 had mild OSA, and 17 had moderate to severe (MS) OSA. Each group had similar questionnaire scores, similar response time and accuracy for the different ANT conditions. There are alterations in the processing of three separate components of the attentional network in children with OSA. The amplitude of the N3 component at the FZ electrode in the MS OSA group was lower than that of the non-OSA and mild OSA groups (all P< 0.05). In the executi control network phase, the energy of alpha band was higher in the MS OSA group than in the mild OSA group (Z=− 2.624, P=0.026). The mean amplitude of the N3 component at the FZ electrode was correlated with the obstructive apnea-hypopnea index (OAHI) (r=0.232, P=0.038).Conclusion: Attention impairment was observed as a reduced N3 in the frontal area in the MS OSA group, which was correlated with the OAHI. However, questionnaire and behavioral performance did not differ significantly between groups. These findings suggest that the N3 amplitude is a sensitive neuroelectrophysiological marker of OSA-related cognitive impairment.Keywords: OSA, child, attention, event-related potential, time-frequency